FABRICATION OF EPOXY COMPOSITES REINFORCED WITH BAMBOO FIBERS - Khazal Hussain, Mohammed; H. Abbas, Salman; M. Younis, Younis; Abdul Rahman, Muhamed; Jamel , Thabit (Journal of Applied Engineering Science, 2020)
This study aims to enhance the mechanical properties of polymer material using type of natural fiber. Bamboo fiber considered the strongest between the natural fibers group, it have low density, high mechanical strength in addition to its availability makes it economically viable and have potential for used as engineering material. The study is concerned with evaluate some of the mechanical properties (Tensile strength, Bending strength, Impact strength) for the resultant composite reinforced with 10, 20 and 30 vol.% of bamboo fibers, as compared with received material. With the natural reinforcement, the optimum mechanical properties in comparison with the as received epoxy were achieved. The results indicated that the tensile strength increased from 13.51 MPa to 33.50 MPa (that is a percentage increase of 150 %), also the bending strength increased from 24.25 MPa to 44.5 MPa (that is a percentage increase about 83 %), as well as, the increase of the impact strength from 41 kJ/m2 to 69 kJ/m2 (that is a percentage increase about 68 %).
Keywords: polymer matrix composite; bamboo fiber; epoxy; mechanical properties; ultimate tensile strength; impact resistance